Four Order Electrostatic Discharge Circuit Model and its Simulation - Ke Wang; Jinshan Wang; Xiaodong Wang (Institute of Advanced Engineering and Science, 2012)
According to the international electrotechnical commission issued IEC61000-4-2 test standard, through the electrostatic discharge current waveform characteristics analysis and numerical experiment method, and construct a new ESD current expression. Using Laplasse transform, established the ESD system mathematical model. According to the mathematical model, construction of passive four order ESD system circuit model and active four order ESD system circuit model, and simulation. The simulation results meet the IEC61000-4-2 standard, and verify the consistency of the ESD current expression, the mathematical model and the circuit model. DOI: http://dx.doi.org/10.11591/telkomnika.v10i8.1632